Escapism and motivation: understanding K-pop fans well-being and identity - Nur Ayuni Mohd Jenol; Nur Hafeeza Ahmad Pazil (Penerbit Universiti Kebangsaan Malaysia, 2020)
K-pop is a relatively new genre but its fanbase has grown massively in Malaysia for the past few decades. It is also evident that the daily lives of Malaysians have incorporated Korean culture in various social aspects. Thus, this study seeks to explore the well-being of local K-pop fans by underlining the objective to understand the meaning of being a K-pop fan. In order to describe and analyse the social nuances of the well-being being a K-pop fan, several concepts from sociology as well as fan studies were plotted to assist this research such as para-social relationship, identity and social identity, the concept of meaning as well as participatory culture. A qualitative approach was employed by using participant observation and semi-structured in-depth interviews to get into the experiences, views, values, and lifestyles of K-pop fans. Participant observation was conducted in K-pop concerts and fan events to observe fan practices. As for the semi-structured in-depth interview, a total number of eight participants were selected to provide an understanding of K-pop fan's well-being through their experiences and feelings. This study concludes that being a K-pop fan carries its special meaning that transcends a fan of a music genre. It varies from providing a platform for escapism as well as emotional and motivational support through a para-social relationship. Although fan and idol is usually seen as one-sided relationship, it has benefitted the fan’s well-being in some way. This study also proves that the fans can also be seen as active producers and content creators which contradict to the notion of fan as a passive entity.